Gamma rays, EMS and DES induced changes on cytology of bhendi [Abelmoschus esculentus (L.) Moench] - P. Pavadai, R. Elangovan and (Journal of Scientific Agriculture, 2017)
Mutation breeding in crop plants such as bhendi (Abelmoschus esculentus (L). Moench) is a successful approach in change of product having narrow genetic base. In the present study to the determine the effect of physical mutagen such as gamma rays and chemical mutagens such as Ethyl methane sulphonate (EMS) and Diethyl sulphate (DES) were used. The seeds were treating with different doses/concentration of Gamma irradiation (10KR, 20KR, 30KR, 40KR, 50KR and 60KR), EMS and DES (0.1, 0.2, 0.3, 0.4, 0.5, and 0.6%) for six hours were applied to 200 seed sample of each concentration and one respective control on bhendi. plants of four generations viz., M1, M2, M3 and M4. The cytological analysis, for example, chromosomal number was watched and recorded for images. The maximum changes of chromosome were observed in 50 KR of gamma rays and 0.4 % of EMS treatments than the other physical and chemical mutagens. The length and shape of chromosome for varied in treated plants than the untreated plants.